Theatrical Tectonics: The Mediating Agent for a Contesting Practice - Gevork Hartoonian (Footprint)
This paper posits the idea that the theme of agency in architecture is parallactic. It discusses the tectonic as an agent through which architecture turns into a state of constant flux. The intention is to promote a discourse of criticality, the thematic of which is drawn from the symptoms that galvanise architecture’s rapport with the image-laden culture of late capitalism. In an attempt to log the thematic of a contested practice, this essay will re-map the recent history of contemporary architecture.